Investigating students' situation-specific emotional state and motivational goals during a learning project within one primary school classroom. (2nd January 2019) - Järvenoja, Hanna; Malmberg, Jonna; Järvelä, Sanna; Näykki, Piia; Kontturi, Heikki
ABSTRACT: This study explores fluctuation in students' emotional state and motivational goals during a learning project that requires self-regulation. The research asks the following questions: (1) How do students' emotional state and motivational goal fluctuate between the gStudy learning sessions during a two-month project? (2) How do students with different situational motivation describe their use of motivation regulation strategies? and (3) How is students' situational motivation associated with their learning outcomes? The students ( N = 20) in one classroom evaluated their emotional state and motivational goals repeatedly with an emotion awareness tool during a two-month-long science project. At the end of the project, they completed a learning test and were interviewed about their regulation strategies. The results show that the students' situational motivation fluctuated in the course of the learning project. The students with a trend of a low situational motivation reported particularly the use of performance and mastery self-talk strategies, the students with moderate situational motivation emphasised environmental structuring and self-consequating, while the students with high situational motivation reported the use of self-consequating and interest enhancement strategies. The students typically reporting high or moderate situational motivation gained significantly more inquiry learning skills compared to their peers with low situational motivation.